Race, Depressive Symptoms, and All-Cause Mortality in the United States - Assari, Shervin; Moazen-Zadeh, Ehsan; Lankarani, Maryam Moghani; Micol-Foster, Valerie (Frontiers in Public Health, 2016)
Purpose Despite the well-established association between baseline depressive symptoms and risk of all cause-mortality, limited information exists on racial differences in the residual effects of baseline depressive symptoms above and beyond socioeconomic status (SES) and physical health on this link. The current study compared Blacks and Whites for the residual effects of depressive symptoms over SES and health on risk of long-term all-cause mortality in the U.S. Methods Data were obtained from the Americans’ Changing Lives Study, a nationally representative longitudinal cohort of U.S. adults with up to 25 years of follow-up. The study followed 3,361 Blacks and Whites for all-cause mortality between 1986 and 2011. The main predictor of interest was baseline depressive symptoms measured at 1986 using an 11-item Center for Epidemiological Studies-Depression scale. Covariates included baseline demographics (age and gender), SES (education and income), and health [chronic medical conditions (CMCs), self-rated health (SRH), and body mass index (BMI)] measured at 1986. Race (Black versus White) was the focal moderator. We ran a series of Cox proportional hazard models in the pooled sample and also stratified by race. Results In the pooled sample, higher depressive symptoms at baseline were associated with higher risk of all-cause mortality except when the CMC, SRH, and BMI were added to the model. In this later model, race interacted with baseline depressive symptoms, suggesting a larger effect of depressive symptoms on mortality among Whites compared to Blacks. Among Whites, depressive symptoms were associated with increased risk of mortality, after controlling for SES but not after controlling for health (CMC, SRH, and BMI). Among Blacks, depressive symptoms were not associated with mortality before health was introduced to the model. After controlling for health, baseline depressive symptoms showed an inverse association with all-cause mortality among Blacks. Although the effect of baseline depressive symptoms on mortality disappeared after controlling for health among Whites, SRH did not interfere (confound) with the effect of depressive symptoms on mortality among Blacks. Conclusion The effect of depressive symptoms on increased risk of all-cause mortality, which existed among Whites, could not be found for Blacks. In addition, race may modify the roles that SES and health play regarding the link between depressive symptoms and mortality over a long period of time.